2005
DOI: 10.1021/jp0441240
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Size Distribution of Gold Nanoparticles under Picosecond Laser Pulses

Abstract: The evolution of size distributions of gold nanoparticles under pulsed laser irradiation (Nd:YAG, lambda = 355 nm, pulse width 30 ps) was carefully observed by transmission electron microscopy. Interestingly, the initial monomodal size distribution of gold nanoparticles turned into a bimodal one, with two peaks in the number of particles, one at 6 nm and the other at 16-24 nm. The sizes for small particles depended very little on the irradiated laser energy. This change is attributed to laser-induced size redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
140
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(152 citation statements)
references
References 46 publications
8
140
2
2
Order By: Relevance
“…The size distribution of the Bi 2 O 3 nanoparticle shows a bi-modal. Similar size distributions were reported by Link [27] and Inasawa [28]. They suggested this phenomenon was attributed to laser-induced size reduction of the large size nanoparticles followed by the formation of small particles.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…The size distribution of the Bi 2 O 3 nanoparticle shows a bi-modal. Similar size distributions were reported by Link [27] and Inasawa [28]. They suggested this phenomenon was attributed to laser-induced size reduction of the large size nanoparticles followed by the formation of small particles.…”
Section: Resultssupporting
confidence: 84%
“…They suggested this phenomenon was attributed to laser-induced size reduction of the large size nanoparticles followed by the formation of small particles. Laser-induced size reduction is a common phenomenon which has been reported by many researchers and its kinetic processes also have been extensively studied [27,28]. Therefore, we suggested the bi-modal distribution of Bi 2 O 3 nanoparticle ablated by femtosecond laser was ascribed to laser-induced size reduction.…”
Section: Resultsmentioning
confidence: 76%
“…Because of subsequent aggregation, coalescence and fusion of NPs, other nanostructures including nanorods, nanobipyramids, nanoprisms and nanodisks can form, where the structures of the products strongly depend on the light wavelength, light intensity and capping ligands. [10][11][12][13][14][15] The control of the morphology and size of the metallic NPs by light not only provides a unique avenue of synthesis but also allows one to modulate their surface plasmon properties in a highly dynamic fashion. 15 In previous studies, however, the prevailing methods for detecting the morphological change of NPs under light irradiation, e.g., time-resolved or static optical scattering and absorption spectroscopies only provided indirect information of the NPs morphology including aggregation size and fractal dimension, which have limited spatiotemporal resolution.…”
Section: Main Textmentioning
confidence: 99%
“…One of these points is the existence of surface melting, i.e., a coexistence of a liquid-like layer of atoms at the surface with the solid core material at temperatures below the respective melting point. 6,7 While this effect seems to be very basic, there is still a lack of unambiguous experimental proof regarding the details, in particular for gold nanoparticles.Inasawa et al 8 have tried to investigate the shape transformation of elongated particles on a surface induced by static heating (ex situ) and concluded that a transformation into spheres takes places at temperatures as low as 400°C. A similar, very recent study has shown that nanorods with a large aspect ratio of the axes can be transformed at 200°C into spheres and partial relaxation occurs much earlier (100°C).…”
mentioning
confidence: 99%